Accounting Information Systems Drive Financial Efficiency in Arab SMEs - Herez, Qassim Mahal (Academia Open, 2025)
General Background: Small and Medium Enterprises (SMEs) are pivotal to economic development, yet often struggle with financial inefficiencies. Specific Background: In Arab countries such as Egypt, Jordan, and Iraq, SMEs face compounded challenges due to outdated financial practices and limited technological integration. Knowledge Gap: While AIS benefits are well documented in developed economies, limited comparative research exists on their impact in Arab SMEs, particularly regarding performance metrics and adoption barriers. Aims: This study investigates the influence of Accounting Information Systems (AIS) on financial performance, operational efficiency, and decision-making among SMEs in Egypt, Jordan, and Iraq. Results: Using mixed methods, the study reveals that AIS adoption significantly improves financial reporting accuracy (up to 50% error reduction), saves 12–20 weekly hours on financial tasks, and lowers operational costs by 18–25% annually. Regression analysis confirms statistically significant positive impacts across all metrics, strongest in Egypt, moderate in Jordan, and weakest in Iraq due to infrastructural and political constraints. Novelty: The study offers a cross-country comparative analysis within the Arab context and develops a model linking AIS adoption to specific performance outcomes. Implications: Findings support targeted policy interventions, training programs, and infrastructure development to enhance AIS adoption, thus strengthening SME competitiveness and regional economic resilience. Highlight : AIS adoption improved financial accuracy, cut costs by up to 25%, and saved 12–20 hours weekly. Key barriers include high implementation costs, skill gaps, and resistance to change. Egypt showed the strongest AIS benefits; Iraq lagged due to infrastructure and political issues. Keywords : AIS, SMEs, Financial Performance, Operational Efficiency, Arab Countries